Construction of an alpaca immune antibody library for the selection of nanobodies against Drosophila melanogaster proteins - Qiu, Jianxiang; Li, Jie; Zhang, Zhen; Dong, Shirui; Ling, Xiaomei; Fang, Zhixin; Ling, Quanshou; Huang, Zhixin (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction:Drosophila melanogaster is a model organism for studying developmental biology and human neural disorders. Nanobodies are the variable domains of the heavy chains of camelid heavy-chain antibodies (VHHs) with high affinity to their antigens and have applications in basic research, similar to traditional antibodies. In addition, nanobodies acting as functionalized antibodies or protein binders have become an additional valuable approach in Drosophila. This study aimed to develop a VHH library against Drosophila proteins and confirm its availability by retrieving some Drosophila protein-specific nanobodies from the library. Methods: An alpaca was first immunized with Drosophila embryo lysate and then its lymphocytes were isolated. Total RNA was extracted and cDNA was synthesized. The vhh sequences were amplified by two round PCR, which were then ligated to a phage display vector pADL-10b. The ligation products were transduced into SS320 competent cells to generate a VHH library. From this library, nanobodies against CG7544, Myc, and CyclinE was enriched and screened by phage display technology and ELISA. DNA sequences of identified nanobodies were cloned into pADL-10b-Flag-His for expression and purification in Escherichia coli SS320. Binding ability of purified nanobodies with corresponding antigens were determined by ELISA and surface plasmon resonance in vitro. Results: In this study, an immune VHH library against Drosophila embryo proteins was generated with a capacity of 3 × 107. From this library, eight nanobodies against three Drosophila proteins, Myc, CyclinE, and CG7544, were identified and the DNA sequences of these nanobodies were obtained. These nanobodies were successfully expressed and purified from Escherichia coli SS320, and were demonstrated to bind corresponding antigens with high affinity in vitro. Moreover, the equilibrium constant between the highest enriched nanobodies and corresponding antigens were calculated. Conclusion: In summary, we report the availability of an immune VHH library and a highly efficient panning strategy for nanobodies against proteins in Drosophila.